Risk Justice in Non-Profit Sharing Contracts in Indonesian Islamic Banking from the Perspective of Maqashid Shariah - Sahban; Zainuddin; Wahida (Yayasan Vifada Cendikia Indonesia, 2025)
Purpose: This research analyzes risk justice in non-profit sharing contracts in Indonesian Islamic banking from the perspective of maqashid shariah, particularly in relation to murabahah, ijarah, and istishna contracts. Research Design and Methodology: This research uses a normative legal method with statute and conceptual approaches. The analysis examines Islamic banking regulations, DSN-MUI fatwa, Islamic legal principles, and scholarly literature to assess whether the structure of non-profit sharing contracts reflects proportional, transparent, and substantive risk distribution. Findings and Discussion: The study finds that the dominance of non-profit sharing contracts in Indonesian Islamic banking has created a risk distribution problem, especially when contractual clauses and financing practices tend to shift economic burdens to customers while banks retain predetermined margins. This condition weakens the substance of sharia contracts and may contradict the principles of al-ghunm bil ghurm and al-kharaj bil dhaman. From the maqashid shariah perspective, particularly hifzh al-mal, risk justice must be reconstructed through distributive, procedural, and substantive justice. The proposed normative reconstruction requires clearer contract clauses, stronger regulatory standards, consistent DSN-MUI fatwa implementation, effective OJK supervision, and an active role of the Sharia Supervisory Board. Implications: This research contributes a normative reconstruction model for strengthening risk justice in Indonesian Islamic banking so that sharia contracts are not only formally valid but also materially fair and aligned with maqashid shariah.